Fostering Creativity and Critical Thinking in Schools: Strategies for 21st Century Education - Farhan Ali (Global Journal of Multidisciplinary and Applied Sciences, 2023)
Creativity and critical thinking are essential skills for success in the 21st century, yet schools often face challenges in fostering these abilities among students. This paper examines the importance of creativity and critical thinking in education, explores strategies that schools can employ to nurture these skills, and discusses the challenges educators face in cultivating these competencies. The study emphasizes the need for a shift in traditional teaching methods towards more inquiry-based, student-centered approaches that encourage problem-solving, collaboration, and innovative thinking. Drawing on best practices and examples from successful educational institutions, this paper provides recommendations for integrating creativity and critical thinking into school curricula across various disciplines. The findings suggest that when schools actively promote these skills, they prepare students to navigate complex problems and contribute to a rapidly changing world.